Enhancing power quality of PV-DSTATCOM integrated grid with modified adaptive LMS control - Lolamo, Mathewos; Kumar, Rajan; Sharma, Veena (Electrical engineering, 2025)
This article presents a modified adaptive control for a single-stage solar photovoltaic-distribution static compensator (PV-DSTATCOM) connected to the three-phase grid. The primary aim of this system is to improve power quality while delivering solar PV energy to the load and grid. The proposed system incorporates a perturb and observe-based maximum power point tracking technique to capture the solar PV array’s peak power consistently. Moreover, an adaptive anti-Hebbian learning-based least mean square (AHLMS) control technique produces active and reactive reference grid currents and controls the voltage source converter’s switching operation. This algorithm precisely controls the PV-DSTATCOM, exhibiting superior capabilities in modifying weights, minimizing errors, and autonomously optimizing parameters in response to variations in solar irradiance, imbalances, and nonlinearity of loads. Hence, it enhances PQ by compensating reactive power, eliminating harmonics, regulating DC-bus and terminal voltages, and improving power factor. The source current is sinusoidally balanced with lower harmonics adhering to IEEE-519 standard. MATLAB/Simulink simulation results and comparative analyses with recent publications demonstrate the proposed algorithm’s outperformance, showcasing its effectiveness in transient and steady-state responses under intermittent sunlight, nonlinearity, and load imbalances.